The effect of simvastatin on the regeneration of surgical cavities in the femurs of rabbits - Rosselli, Jose Eduardo Gomes Cardim (2014)
PURPOSE:To evaluate the effect of a local application of simvastatin gel in repairing bone defects in the femurs of rabbits.METHODS:Two standard surgical cavities were created in the femoral epiphysis of 18 rabbits. In the simvastatin group (SG), the cavities were filled with a collagen sponge soaked in 0.5 ml of a simvastatin (1 mg) gel, and the cavities were covered with a biological membrane. The bone cavities in the second group (control group) were filled with a blood clot and covered with a biological membrane. On the 7th, 21st and 42nd days, six animals in each group were euthanized, and the femurs were subject to histological evaluation (vascularity, fibrosis, reactive bone formation, osteoblasts, and osteoclasts) and immunohistochemical (anti-VEGF and anti-osteocalcin) analysis. The results were analyzed using a Wilcoxon test (p<0.05).RESULTS:There were significant differences between the two groups: the SG had greater scores in comparison with the CG in terms of the degree of vascularity on the 7th and the 21st days, fibrosis on the 21st day, bone formation reaction on the 21st and the 42nd days and the number of osteoblasts and osteoclasts on the 42nd day. The immunohistochemical expression was also greater for osteocalcin and VEGF on the 7th, 21st and 42nd days.CONCLUSION:Surgical defects created in rabbit femurs were treated locally with simvastatin gel to stimulate bone repair, which promoted an ameliorative effect in the morphological and immunohistochemical markers of bone regeneration.